2023
DOI: 10.2147/cia.s404082
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophil: A New Circulating Biomarker for Risk of Poor Outcome in Stroke Patients Undergoing Mechanical Thrombectomy

Abstract: Objective Acute ischemic stroke (AIS), caused by occlusion of large vessel, is a serious life-threatening disease. This study aimed to comprehensively investigate the association of 14 common and readily available circulating biomarkers with the 90-day modified Rankin Scale (mRS) score in patients undergoing mechanical thrombectomy (MT). Methods This study included patients with anterior circulation large vessel occlusive stroke treated with MT from 05/2017 to 12/2021. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Studies have shown that AIS causes a sudden rise in the circulation of neutrophils and a decline in circulating lymphocytes. [30,31] Thus, NLR is a reliable indicator of inflammation in AIS. In previous research, [32] high NLR values were related to adverse outcomes, and NLR has been identified as a mortality indicator for patients with severe brain trauma injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that AIS causes a sudden rise in the circulation of neutrophils and a decline in circulating lymphocytes. [30,31] Thus, NLR is a reliable indicator of inflammation in AIS. In previous research, [32] high NLR values were related to adverse outcomes, and NLR has been identified as a mortality indicator for patients with severe brain trauma injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have found the influence of factors such as age, gender, smoking, and alcohol consumption on stroke prognosis. A thorough examination of 39 research studies, encompassing a collective participation of 359,783 individuals, unveiled a notable disparity in the prevalence of diabetes between ischemic strokes (IS) (33%, 95% CI ~ [28][29][30][31][32][33][34][35][36][37][38] and hemorrhagic strokes (26%, 95% CI ~ [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]. Furthermore, the analysis established a clear association between both acute hyperglycemia and diabetes and adverse post-stroke outcomes, whether ischemic or hemorrhagic.…”
Section: Introductionmentioning
confidence: 99%
“…Neutrophils, eosinophils, and neutrophil-to-lymphocyte ratio were independent factors for poor prognosis after mechanical thrombectomy in AIS patients. [ 30 ] High platelet count and high-sensitivity C-reactive protein (HS-CRP) were significantly associated with adverse clinical outcomes. [ 31 ] High-density lipoprotein (HDL) was associated with mild cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Reduced eosinophil levels are associated with poor prognosis after mechanical thrombectomy in patients with acute ischemic stroke (AIS), but the underlying mechanism of this association is unclear [ 1 , 2 ]. In contrast, in our previous study, lower eosinophil levels were associated with a higher incidence of stroke-associated pneumonia (SAP); in addition, SAP was found to play an important mediating role in the association between eosinophilia and poor prognosis.…”
Section: Introductionmentioning
confidence: 99%